RETOLD: On the Way for a Digital Future of Documentation in Open-air Museums – User Requirements for Data Entry and a Management Product for the RETOLD-Project - Cordula Hansen; Rüdiger Kelm (EXARC Journal)
As part of the RETOLD project, which runs from 2020 until 2024 and is funded by the Creative Europe Programme, Nüwa Digital Media Production Studios (Ireland) in collaboration with the Archaeological-Ecological Centre Albersdorf (AÖZA, Germany) have carried out a year-long user research project for a future digital tool, that will enable open air museums to collect and manage data, which are relevant to their practice.